Ambrosius Spiera: A @Fifteenth-Century Italian Preacher and Scholar - Rentner, Ronald M. (Church history, 1974)
Our attempts to piece together the mosaic of ideas and events during the late medieval period have been enriched in recent years by the increased attention given to the study of sermons. Sentence commentaries, summae and tracts are the bedrock for the study of medieval theology, but we also wish to know what was being preached.